2012
DOI: 10.1111/j.1399-3062.2011.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive fatal hemorrhagic pneumonia caused by Stenotrophomonas maltophilia in hematologic malignancy

Abstract: Hemorrhagic S. maltophilia pneumonia rapidly progresses and is fatal in patients with hematologic malignancy. Attention should be particularly paid to the neutropenic phase early after HSCT or prolonged neutropenia due to engraftment failure. A prompt trimethoprim-sulfamethoxazole-based multidrug combination regimen should be considered to rescue suspected cases of S. maltophilia pneumonia in these severely immunosuppressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Prolonged hospitalization, staying in ICU, and mechanical ventilation are reported as precipitating risk factors for S. maltophilia infections (22,26,(29)(30)(31). Time of acquiring infection after hospitalization (median; min-max values were presented in Table 1) was not different in the two groups, and more than half of the patients in the groups were in ICU.…”
Section: Discussionmentioning
confidence: 93%
“…Prolonged hospitalization, staying in ICU, and mechanical ventilation are reported as precipitating risk factors for S. maltophilia infections (22,26,(29)(30)(31). Time of acquiring infection after hospitalization (median; min-max values were presented in Table 1) was not different in the two groups, and more than half of the patients in the groups were in ICU.…”
Section: Discussionmentioning
confidence: 93%
“…However, it forms biofilm on the surface of medical devices as well as pulmonary epithelial cells, has great influence in respiratory infection, and is becoming multi-drug resistant [20,21,22]. As the study of Araoka et al has reported that pneumonia due to Stenotrophomonas maltophilia in hematologic cancer patients has 100% mortality, it can cause lethal result in immunosuppressed patients though its pathogenicity is low [23,24]. It is worth paying attention to that lately, nosocomial infection of Stenotrophomonas maltophilia is increasing through medical devices inserted after surgery [25], and the detection rate of Stenotrophomonas maltophilia, which is strongly antibiotic-resistant [20], is high in the testing devices in emergency room, which is often an entrance and exist of immunosuppressed patients.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Occasionally, distinguishing between colonization and infection can be problematic (1–3). S. maltophilia infections can be complicated by septic shock, respiratory failure, pulmonary hemorrhage, metastatic cellulitis, tissue necrosis that may be extensive, septic thrombophlebitis, disseminated infection, and death (5–8, 11). …”
Section: Infections Caused By S Maltophiliamentioning
confidence: 99%
“…In patients with HM and in recipients of HSCT having severe lung infection caused by S. maltophilia , life-threatening pulmonary alveolar hemorrhage (PAH) causing acute respiratory failure has been reported (7, 8, 3032). The risk factors for PAH in these patients include prolonged cytopenias and high C-reactive protein levels at the onset of BSI or pneumonia (7, 8).…”
Section: Pneumonia Caused By S Maltophiliamentioning
confidence: 99%